Farmland values and bidder behavior in first-price land auctions - Carsten Croonenbroeck; Martin Odening; Silke Hüttel (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2018)
Within this paper, we aim to investigate asymmetries among bidders in land auctions that may entail non-competitive prices. Using representative data for Eastern Germany including winning bids, bidder characteristics, and land amenities, we pursue a structural approach to derive distributions of latent land values for different bidder groups. By applying nonparametric techniques, we cannot find evidence for asymmetric bidder structures while differentiating between legal entities, tenancy status, and nationality of bidders. Our findings challenge the hypothesis that land privatization via auctions discriminates against certain buyer groups - an argument that is often used to justify stricter regulation of agricultural land markets.
Keywords: C57; D44; Q12; Q15; 330; First-Price Sealed Bid Land Auctions; Structural Estimation; Buyer Heterogeneity